O12.2 Co-infection and macrolide antimicrobial resistance (AMR) of mycoplasma genitalium with neisseria gonorrhoeae and chlamydia trachomatis, in females, heterosexual males, and men-who-have-sex-with-men. (8th July 2017) - Broad, Claire Elizabeth; Harding-Esch, Emma; Harrison, Mark; Pond, Marcus James; Tan, Ngeekeong; Okala, Sandra; Soares, Clare; Fuller, Sebastian; Sadiq, Syed Tariq
Abstract : Introduction: Population-based prevalence estimates of Mycoplasma genitalium (MG), Chlamydia trachomatis (CT) and Neisseria gonorrhoeae (NG) in men and women in England are: 1.2% and 1.3%; 1.1% and 1.5%; and <0.1%, respectively. In sexual health clinics (SHCs), NG and CT are routinely tested for, whereas MG is not. Undiagnosed MG co-infection threatens and complicates empirical therapy of CT and NG, where azithromycin use may aid further spread of macrolide antimicrobial resistance (AMR). We assessed co-infection and macrolide AMR prevalence in symptomatic patients accessing three London SHCs. Methods: Patients aged ≥16 years with symptoms of an STI provided samples: vulvovaginal swab (females), first void urine (men-who-have-sex-with-women (MSW) and men-who-have-sex-with-men (MSM)), pharyngeal and rectal swabs (MSM). Routine clinic CT/NG results were obtained and FTD Urethritis Plus kit used for MG detection. Resistance was determined using Sanger sequencing. Results: Prevalence of NG only infection in females, MSW and MSM was 0.3% (95%CI 0–1.8), 3.5% (1.6–7.3) and 31.0% (21.4–42.5), respectively. MG only prevalence was 5.3% (3.3–8.4), 14.9% (10.4–21.0) and 11.3% (5.8–20.7), respectively. CT only prevalence was 5.6% (3.5–8.7), 15.5% (10.9–20.6) and 5.6% (2.2–13.6), respectively. MG-NG co-infection was in MSW only (0.6%, 0.1–3.2), representing 2.4% (0.4–12.3) of NG infections. CT-MG co-infection was in females and MSW (1.6%, 0.7–3.8% and 2.3%, 0.9–5.8, respectively), together representing 13.0% (7.0–23.0) of CT infections. CT-NG co-infection was in all groups (females: 0.3%, 0–1.8; MSW: 2.3%, 0.9–5.8; MSM 7.0%, 3.1–15.5). MG-NG-CT infection was found in females (0.7%, 0.2–2.4), representing 16.7% (4.7–44.8) of NG-CT infections. 64.9% (37/57) of MG samples sequenced were macrolide resistant (67.0% (21/31) from MSW). Conclusion: With 13.0% and 2.4% of CT and NG infections respectively being co-infected with MG, and two-thirds MG infections displaying macrolide AMR, use of azithromycin for symptomatic CT/NG treatment in the absence of MG testing should be reconsidered.